Racial/Ethnic Variation in the Impact of the Affordable Care Act on Insurance Coverage and Access Among Young Adults - VanGarde, Aurora; Yoon, Jangho; Luck, Jeff; Mendez-Luck, Carolyn A. (American journal of public health (1971), 2018)
Objectives. To examine the impact of the Affordable Care Act’s (ACA’s) 2010 parental insurance coverage extension to young adults aged 19 to 25 years on health insurance coverage and access to care, including racial/ethnic disparities. Methods. We pooled data from the Behavioral Risk Factor Surveillance System for the periods 2007 to 2009 and 2011 to 2013 (n = 402 777). We constructed quasiexperimental difference-in-differences models in which adults aged 26 to 35 years served as a control group. Multivariable statistical models controlled for covariates guided by the Andersen model for health care utilization. Results. On average, insurance rates among young adults increased 6.12 percentage points after ACA implementation (P < .001). All racial/ethnic groups experienced increases in coverage. However, the impact varied by race/ethnicity and was largest for Whites. Young adults had a 2.61 percentage point (P < .001) decrease in experiencing barriers to health care because of cost issues after the ACA, with variation by race/ethnicity. Conclusions. The ACA’s expansion had a significant positive effect for young adults acquiring health insurance and reducing cost-related barriers to accessing health care. However, racial/ethnic disparities in coverage and access persist. Public Health Implications. Policies not dependent on parental insurance could further increase access and reduce disparities.